Matrix-Applied Characterized Autologous Cultured Chondrocytes Versus Microfracture: Five-Year Follow-up of a Prospective Randomized Trial. Issue 6 (May 2018) - Brittberg, Mats; Recker, David; Ilgenfritz, John; Saris, Daniel B.F.; ,
Background: Matrix-based cell therapy improves surgical handling, increases patient comfort, and allows for expanded indications with better reliability within the knee joint. Five-year efficacy and safety of autologous cultured chondrocytes on porcine collagen membrane (MACI) versus microfracture for treating cartilage defects have not yet been reported from any randomized controlled clinical trial. Purpose: To examine the clinical efficacy and safety results at 5 years after treatment with MACI and compare these with the efficacy and safety of microfracture treatment for symptomatic cartilage defects of the knee. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: This article describes the 5-year follow-up of the SUMMIT (Superiority of MACI Implant Versus Microfracture Treatment) clinical trial conducted at 14 study sites in Europe. All 144 patients who participated in SUMMIT were eligible to enroll; analyses of the 5-year data were performed with data from patients who signed informed consent and continued in the Extension study. Results: Of the 144 patients randomized in the SUMMIT trial, 128 signed informed consent and continued observation in the Extension study: 65 MACI (90.3%) and 63 microfracture (87.5%). The improvements in Knee injury and Osteoarthritis Outcome Score (KOOS) Pain and Function domains previously described were maintained over the 5-year follow-up. Five years after treatment, the improvement in MACI over microfracture in the co-primary endpoint of KOOS pain and function was maintained and was clinically and statistically significant ( P = .022). Improvements in activities of daily living remained statistically significantly better ( P = .007) in MACI patients, with quality of life and other symptoms remaining numerically higher in MACI patients but losing statistical significance relative to the results of the SUMMIT 2-year analysis. Magnetic resonance imaging (MRI) evaluation of structural repair was performed in 120 patients at year 5. As in the 2-year SUMMIT (MACI00206) results, the MRI evaluation showed improvement in defect filling for both treatments; however, no statistically significant differences were noted between treatment groups. Conclusion: Symptomatic cartilage knee defects 3 cm 2 or larger treated with MACI were clinically and statistically significantly improved at 5 years compared with microfracture treatment. No remarkable adverse events or safety issues were noted in this heterogeneous patient population.